Speaking proficiency of young language students: A discourse-analytic study. (January 2019) - Hsieh, Ching-Ni; Wang, Yuan
This study investigated a range of fluency, grammar, vocabulary, and content features of young language students' speaking performances, using a discourse-analytic approach. In total, 179 test takers' responses to the speaking section of the TOEFL Junior ® Comprehensive test were selected for analysis. Mixed-design ANOVAs were used to compare 21 spoken discourse features across four proficiency levels and two task types (i.e., a picture narration task and an integrated listen/speak task). The discourse features largely differentiated test takers across proficiency levels. Task types showed some impact on measures of grammar, vocabulary, and content, but had no influence on features of fluency. Findings of the study have implications for the language development of young second and foreign language students and provide insights into language assessment task design for this population.